A Systematic Review of the Effectiveness of Warming Interventions for Women Undergoing Cesarean Section. (30th September 2014) - Munday, Judy; Hines, Sonia; Wallace, Karen; Chang, Anne M.; Gibbons, Kristen; Yates, Patsy
ABSTRACT Background Women undergoing cesarean section are vulnerable to adverse effects associated with inadvertent perioperative hypothermia, but there has been a lack of synthesized evidence for temperature management in this population. This systematic review aimed to synthesize the best available evidence in relation to preventing hypothermia in mothers undergoing cesarean section surgery. Methods Randomized controlled trials meeting the inclusion criteria (adult patients of any ethnic background, with or without comorbidities, undergoing any mode of anesthesia for any type of cesarean section) were eligible for consideration. Active or passive warming interventions versus usual care or placebo, aiming to limit or manage core heat loss in women undergoing cesarean section were considered. The primary outcome was maternal core temperature. A comprehensive search with no language restrictions was undertaken of multiple databases from their inception until May 2012. Two independent reviewers using the standardized critical appraisal instrument for randomized controlled trials from the Joanna Briggs Institute Meta‐Analysis of Statistics Assessment and Review Instruments (JBI‐MASTARI) assessed retrieved papers for methodological quality and conducted data collection. Where possible, results were combined in a fixed effects meta‐analysis using the Cochrane Collaboration Review Manager software. Due to heterogeneity for one outcome, random effects meta‐analysis was also used. Results A combined total of 719 participants from 12 studies were included. Intravenous fluid warming was found to be effective at maintaining maternal temperature and preventing shivering. Warming devices, including forced air warming and under‐body carbon polymer mattresses, were effective at preventing hypothermia. However, effectiveness increased if the devices were applied preoperatively. Preoperative warming devices reduced shivering and improved neonatal temperatures at birth. Intravenous fluid warming did not improve neonatal temperature, and the effectiveness of warming interventions on umbilical pH remains unclear. Linking Evidence to Action Intravenous fluid warming by any method improves maternal temperature and reduces shivering during and after cesarean section, as does preoperative body warming. Preoperative warming strategies should be utilized where possible. Preoperative or intraoperative warmed IV fluids should be standard practice. Warming strategies are less effective when intrathecal opioids are administered. Further research is needed to investigate interventions in emergency cesarean section surgery. Larger scale studies using standardized, clinically meaningful temperature measurement time points are required.